Smart drugs among students – multidimensional view on present ways of cognitive enhancement - Pisera, Piotr; Kiełkowicz, Aleksandra; Pactwa, Filip; Popińska, Zuzanna; Żmuda, Bartłomiej; Ślusarczyk, Daniel; Jakubowska, Wiktoria; Żuberek, Michał (Journal of Education, Health and Sport, 2023)
Background: Nootropic drugs, at the beginning of their career, were used in the treatment of diseases such as attention deficit hyperactivity disorder (ADHD), Alzheimer’s disease and narcolepsy. Nowadays, they are becoming more and more popular among students, where they are often called smart drugs or cognitive enhancers. Their properties that improve intellectual abilities and cognitive functions are used to, among other things, improve academic performance. Aim of the study: The purpose of this article was to summarize the current state of knowledge relating to the use of smart drugs among students. This study discusses the multidimensional issues of using this group of drugs. Material and methods: A cross-sectional search of relevant literature was performed in databases using accepted wording. Publications from 2003-2023 were included. The entire process has been supplemented with additional procedures to increase the reliability of this publication. Results: In most sources, the most common representative of smart drugs turned out to be methylphenidate. Nootropics were most often obtained by obtaining a prescription from a doctor, online trading or from friends. The factors motivating the use of substances from this group are primarily the desire to improve academic results, competitiveness and the number of obligations at the university. There are many risks associated with their use, but students are more aware of the positive effects. Conclusion: This paper presents various dimensions of the progressive spread of nootropic drugs. In addition to their undeniably positive effects, there are many risks, which are discussed in this article. Students’ awareness should be formed through appropriate educational methods.